The Victorians and China: Travels with Ships, Ideologies and Literature - Kuehn, Julia (Australasian Journal of Victorian Studies, 2015)
One could argue that the Victorian relations with China began, avant la lettre, in 1793, with Lord Macartney’s famous refusal to kowtow in front of the Chinese Emperor unless he did the same before a portrait of the British monarch. Gone were the days of a romanticised China, as in Coleridge’s “Kubla Khan”; the Macartney Embassy encountered China as a reality, and, more importantly, as a real force to reckon with. The relationship with China – politically, economically, culturally – was not going to be an easy one.